Pengaruh Kekuasaan Kepemimpinan, Pembayaran Kerja Dan Kemampuan Anggota Kepolisian Terhadap Kinerja Anggota Kepolisian Di Polres Pandeglang - Sagitanur Sukmo Anggoro; Ahmad Sugianto; Hida Nurhidayat; M. Iqbal (E-Journal Studia Manajemen, 2022)
In the context of the police, performance is the main focus in establishing legitimacy and fostering cooperation with the community. People who are satisfied with the performance of the police will be more willing to comply with the directions and rules given. however, there are several factors that can reduce performance, namely: weak leadership power, stunted pay for work, and insufficient capacity of police personnel. The purpose of this study was to analyze the relationship between leadership power, work payment, and ability to the performance of the non-commissioned officers of the Pandeglang-Banten Police.This study was an analytic observational study with a cross sectional design. The sample was 60 police personel at POLRES Pandeglang, Banten. The research was conducted in February 2021. The dependent variable is performance and the independent variables are leadership power, payment of work, and the ability of members. Data collection was carried out by means of a questionnaire. Data were analyzed by multiple linear regression analysis. Simultaneously there is a significant influence between leadership power, compensation and ability on the police performance of the Pandeglang Police in Pandeglang Regency (2021).